Comparing the quality of collaborative writing, collaborative prewriting, and individual texts in a Thai EFL context. (June 2018) - McDonough, Kim; De Vleeschauwer, Jindarat; Crawford, William
Abstract: Although previous studies have compared the quality of collaborative writing texts to those written individually without any peer interaction, studies to date have not explored whether collaborative prewriting affords any of the same benefits of collaborative writing. Situated within the collaborative writing research, this study compares the text features and analytic ratings of paragraphs written by EFL students ( N  = 128) at a university in Thailand under three conditions: collaborative writing, collaborative prewriting, or no collaboration. The students' paragraphs were coded for linguistic measures of accuracy (errors/word) and subordination (dependent clauses/clauses), and were rated using a 30-point analytic rubric with three categories (content, organization, and language). The results revealed that the collaborative texts were more accurate than the collaborative prewriting and no collaboration texts, while the collaborative prewriting and no collaboration texts contained more subordination. Issues for future research about the role of collaboration at various stages in the L2 writing process are discussed.